Database quality assessment in research in paramedicine: a scoping review protocol. Issue 7 (14th July 2022) - McDonald, Neil; Kriellaars, Dean; Doupe, Malcolm; Giesbrecht, Gordon; Pryce, Rob T
Abstract : Introduction: The paramedic practice environment presents unique challenges to data documentation and access, as well as linkage to other parts of the healthcare system. Variable or unknown data quality can influence the validity of research in paramedicine. A number of database quality assessment (DQA) frameworks have been developed and used to evaluate data quality in other areas of healthcare. The extent these or other DQA practices have been applied to paramedic research is not known. Accordingly, this scoping review aims to describe the range, extent and nature of DQA practices within research in paramedicine. Methods and analysis: This scoping review will follow established methods for the conduct (Johanna Briggs Institute; Arksey and O'Malley) and reporting (Preferred Reporting Items in Systematic Reviews and Meta-Analyses extension for scoping reviews) of scoping reviews. In consultation with a professional librarian, a search strategy was developed representing the applicable population, concept and context. This strategy will be applied to MEDLINE (National Library of Medicine), Embase (Elsevier), Scopus (Elsevier) and CINAHL (EBSCO) to identify studies published from 2011 through 2021 that assess paramedic data quality as a stated goal. Studies will be included if they report quantitative results of DQA using data that relate primarily to the paramedic practice environment. Protocols, commentaries, case studies, interviews, simulations and experimental data-processing techniques will be excluded. No restrictions will be placed on language. Study selection will be performed by two reviewers, with a third available to resolve conflicts. Data will be extracted from included studies using a data-charting form piloted and iteratively revised based on studies known to be relevant. Results will be summarised in a chart of study characteristics, DQA-specific outcomes and key findings. Ethics and dissemination: Ethical approval is not required. Results will be submitted to relevant conferences and peer-reviewed journals. Trial registration: 10.17605/OSF.IO/Z287T.